Optical Coherence Tomography for Three-Dimensional Imaging in the Biomedical Field: A Review - Zheng, Shu; Bai, Yanru; Xu, Zihao; Liu, Pengfei; Ni, Guangjian (Frontiers in Physics, 2021)
Optical coherence tomography (OCT) has become a novel approach to noninvasive imaging in the past three decades, bringing a significant potential to biological research and medical biopsy in situ, particularly in three-dimensional (3D) in vivo conditions. Specifically, OCT systems using broad bandwidth sources, mainly centered at near-infrared-II, allow significantly higher imaging depth, as well as maintain a high-resolution and better signal-to-noise ratio than the traditional microscope, which avoids the scattering blur and thus obtains more details from delicate biological structures not just limited to the surface. Furthermore, OCT systems combined the spectrometer with novel light sources, such as multiplexed superluminescent diodes or ultra-broadband supercontinuum laser sources, to obtain sub-micron resolution imaging with high-speed to achieve widespread clinical applications. Besides improving OCT performance, the functional extensions of OCT with other designs and instrumentations, taking polarization state or birefringence into account, have further improved OCT properties and functions. We summarized the conventional principle of OCT systems, including time-domain OCT, Fourier-domain OCT, and several typical OCT extensions, compared their different components and properties, and analyzed factors that affect OCT performance. We also reviewed current applications of OCT in the biomedical field, especially in hearing science, discussed existing limitations and challenges, and looked forward to future development, which may provide a guideline for those with 3D in vivo imaging desires.